Mediation as an Alternative to Resolving Problematic Credit in Banking Financial Institutions - Yasid, Muhammad (Rechtsvinding, 2025)
The problem of non-performing loans (NPLs) remains a major challenge for banking financial institutions due to its direct implications for liquidity, profitability, and the stability of the national financial system. To date, resolution of non-performing loans has generally been carried out through litigation, which is known to be time-consuming, expensive, and provides little flexibility for the disputing parties. This study focuses on analyzing the effectiveness of mediation as an alternative for resolving non-performing loan disputes in the banking sector by examining the regulatory framework, implementation practices, and factors determining its success. Using a normative juridical approach and descriptive qualitative analysis methods, this study explores various legal provisions such as Law Number 30 of 1999, PERMA Number 1 of 2016, and POJK Number 18/2018 and POJK Number 61/2020 concerning the LAPS FSS. The results indicate that mediation has the potential to be an efficient, low-cost, and equitable mechanism for resolving non-performing loans, especially for the micro, small, and medium enterprises (MSMEs) and consumer credit segments. However, its implementation remains suboptimal due to the lack of legal requirements, low awareness among the parties, and limited competence of mediators in the financial sector. Therefore, strengthening regulations, increasing the capacity of mediators, and fostering a legal culture that supports peaceful dispute resolution are necessary for mediation to function optimally as an instrument of substantive justice while maintaining the stability of the national financial system.